Differential diagnostics of food allergy as based on provocation tests and laboratory diagnostic assays - Krzych-Fałta, Edyta; Białek, Sławomir; Sybilski, Adam J.; Tylewicz, Aleksandra; Samoliński, Bolesław; Wojas, Oksana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Due to the scale of the phenomenon, food allergies constitute a significant health problem and significantly impair the quality of life of patients. Differential diagnostics, including skin tests, sIgE detection tests, basophil and mast cell activation tests as well as double-blind placebo-controlled food challenge tests, is the gold standard in the diagnosis of food allergies. Recently, increasing attention has been paid to the potential use of intranasal provocation tests in the diagnosis of food allergies. Allergen dose, protocol standardization, assessment of subjective complaints and objectivization of test results are important factors determining the applicability of provocation tests.